Social communication and dynamics of subak culture in the preservation of Ulun Suwi Temple - I Gusti Ngurah Sudiana; I Wayan Wastawa; Nyoman Merta (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: Social communication among heterogeneous communities within the cultural dynamics of the Subak system in the Subak Tegal area of the Bumi Dalung Permai Housing Complex plays a crucial role in the preservation of Ulun Suwi Temple. This article aims to examine the urgency of social communication within the dynamics of Subak culture and its contribution to temple preservation in a socially and spatially transformed environment. Methods: Data were collected through in-depth interviews, document analysis, and field observations. A qualitative descriptive approach was employed for data analysis. Findings: The findings indicate that sustained social communication functions as a mechanism to mitigate value and identity conflicts, prevent declining ritual participation, and reduce the risk of social disintegration. Continuous interaction between Subak Tegal members and non-farmer residents of the Bumi Dalung Permai Housing Complex has facilitated a transformation in the meaning and identity of Ulun Suwi Temple, from an agrarian Subak temple into a unifying symbol of Hindu religious identity within a heterogeneous residential community. The participation of non-farmer Hindus reflects all types of social action as conceptualized by Max Weber, including goal-oriented, value-oriented, affective, and traditional actions. Conclusion: This study concludes that effective social communication between the farming community and the diverse residential community is key to transforming Pura Ulun Suwi from an agrarian symbol into a unifying symbol of religious identity, thereby ensuring the sustainability of cultural heritage amid the challenges of urbanization. Novelty/Originality of this article: This study offers a novel contribution by demonstrating that the preservation of a Subak temple in an urbanized residential setting is not solely dependent on traditional agrarian structures or customary regulations but is significantly shaped by effective social communication that enables cross-group collaboration.